Face adaptation effects show strong and long-lasting transfer from lab to more ecological contexts - Carbon, Claus-Christian; Ditye, Thomas (Frontiers in Psychology, 2012)
A review on recent experiments on figural face aftereffects reveals that adaptation effects in famous faces can last for hours up to days. Such adaptations seem to be highly reliable regarding test–retest designs as well as regarding the generalizability of adaptation across different adaptation routines and adaptations toward different kinds of facial properties. However, in the studies conducted so far, adaptation and the subsequent test phase were carried out in typical laboratory environments. Under these circumstances, it cannot be ruled out that the observed effects are, in fact, episodic learn–test compatibility effects. To test for ecological validity in adaptation effects we used an adaptation paradigm including environmental and social properties that differed between adaptation and test phase. With matched samples (n1 = n2 = 54) we found no main effects of experimental setting compatibility resulting from varying where the tests where conducted (environmental condition) nor any interaction with effects of stimulus compatibility resulting from varying stimulus similarity between adaptation and test phase using the same picture, different pictures of the same person, or different persons (transfer). This indicates that these adaptation effects are not artificial or merely lab-biased effects. Adaptation to face stimuli may document representational adaptations and tuning mechanisms that integrate new visual input in a very fast, reliable, and sustainable way.